A Division of Laborers : Identity and Efficiency in India - Cassan, Guilhem; Keniston, Daniel; Kleineberg, Tatjana (World Bank, Washington, DC, 2021)
Workers' social identity affects their choice of occupation, and therefore the structure and prosperity of the aggregate economy. This paper studies this phenomenon in a setting where work and identity are particularly intertwined: the Indian caste system. Using a new dataset that combines information on caste, occupation, wages, and historical evidence of subcastes’ traditional occupations, the paper shows that caste members are still greatly overrepresented in their traditional occupations. To quantify the effects of caste-level distortions on aggregate and distributional outcomes, the paper develops a general equilibrium Roy model of occupational choice. The authors structurally estimate the model and evaluate counterfactuals that remove castes' ties to their traditional occupations, through their direct preferences, and via their parental occupations and social networks. The findings show that the share of workers employed in their traditional occupation decreases substantially. However, the effects on aggregate output and productivity are very small–and in some counterfactuals even negative–because gains from a more efficient human capital allocation are offset by productivity losses from weaker caste networks and reduced learning across generations. The findings emphasize the importance of caste identity in coordinating workers into occupational networks that enable productivity spillovers.